Sintered magnet with high Ce content and preparation method thereof
By adding high coercive sintered Nd-Fe-B magnet waste to Ce-rich main phase alloys and using in-situ diffusion technology to construct the shell, it is solved that it is difficult to effectively utilize high abundance Ce and sintered Nd-Fe in the prior art. -B magnet waste problem, high Ce content sintered magnets were prepared, achieving balanced utilization of rare earth resources and reducing production costs.
Patent Information
- Application Number
- CN202411671532.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The prior art is difficult to effectively utilize high-abundance rare earth element Ce and sintered Nd-Fe-B magnet waste to prepare sintered magnets with high Ce content and high coercive force, resulting in unbalanced utilization of rare earth resources and high production costs.
By adding sintered Nd-Fe-B magnet waste containing heavy rare earths Dy, Tb and coercive force greater than 20 kOe to the Ce-rich main phase alloy, the main body of the high magnetic crystal anisotropy field is provided by sintered Nd-Fe-B magnet waste. The phase grains were used to construct a shell with a high magnetic crystal anisotropy field on the surface of Ce-rich main phase grains through in-situ diffusion technology to prepare a high Ce content sintered magnet.
The preparation of high Ce content sintered magnets is realized, with better magnetic properties, reducing dependence on non-high abundance rare earth elements, promoting the balanced utilization of rare earth resources, and reducing production costs.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rare earth permanent magnet material preparation, and in particular to a high Ce content sintered magnet and a preparation method thereof. Background Art
[0002] Rare earth permanent magnet materials are the largest application field of rare earth resources, and are also the key basic materials supporting the leapfrog development of strategic emerging industries and future industries such as new energy vehicles, advanced rail transportation equipment, high-end CNC machine tools and robots. Facing major national strategic needs such as "dual carbon" and sustainable development, the rare earth permanent magnet industry has developed rapidly in recent years. The output of sintered Nd-Fe-B magnets has increased year by year, and the demand for rare earths such as Nd, Pr, Dy, and Tb has also increased sharply. Due to the coexistence of rare earth elements in rare earth ores, excessive consumption of Nd, Pr, Dy, and Tb elements for the manufacture of Nd-Fe-B permanent magnets, while accounting for about 70% of the total rare earth reserves and cheap light rare earth elements such as La and Ce, have been largely shelved due to limited market demand, resulting in an unbalanced utilization of rare earth resources in my country. In addition, a large amount of scraps will be generated during the production and processing of sintered Nd-Fe-B magnets, and the increase in the annual output of sintered Nd-Fe-B magnets has also led to a rapid increase in the amount of rare earth permanent magnet secondary resources such as scraps and scrapped magnets that have been discarded after use. Therefore, using high-abundance, low-cost Ce and sintered Nd-Fe-B magnet waste to prepare sintered magnets with high Ce content is an important way to promote the efficient application of rare earth resources in my country, and has very important strategic significance in terms of economic efficiency and sustainable development.
[0003] In terms of Ce element utilization, due to Ce2Fe 14 The intrinsic performance of B is much lower than that of Nd2Fe 14 B and Pr2Fe 14 B, Ce replacing Nd and Pr will reduce RE2Fe 14The intrinsic magnetic properties of the tetragonal phase B lead to a strong magnetic dilution effect. In order to weaken the magnetic dilution effect caused by the introduction of Ce elements, a dual-phase alloy process is currently used to design and prepare a Ce-containing main phase magnetic powder and a Ce-free main phase magnetic powder, which are uniformly mixed in a certain proportion to prepare a multi-main phase Ce-based sintered magnet. Compared with single-main phase magnets, the rare earth elements in a single main phase grain of a multi-main phase magnet are unevenly distributed and present a "core-shell" structure, as well as Ce-rich and Ce-poor grains. The chemical composition heterogeneity caused by the uneven distribution of rare earth elements inside the main phase grains and between grains can effectively weaken the magnetic dilution effect caused by the introduction of Ce. For example, the invention patents 201210315684.5 and 201310090328.2 use a dual-phase alloy process to prepare two quick-setting sheets with different compositions, and obtain the final multi-phase magnet after crushing, powdering, mixing, sintering and heat treatment. At least one quick-setting sheet used contains a Nd-rich 2:14:1 main phase, and the Nd2Fe 14 In the prior art, the dual-phase alloy process for preparing Ce magnets must use Nd-rich quick-solidified sheets and then use hydrogen crushing and air flow milling to prepare magnetic powder as Nd2Fe 14 The source of B grains is obviously not conducive to further reducing the manufacturing cost of Ce magnets and reducing the dependence on Pr and Nd rare earth elements.
[0004] In addition, in response to the increase in the amount of sintered Nd-Fe-B magnet waste, in addition to the traditional remelting and re-refining technology, the use of surface treatment, crushing and powdering, oriented pressing, sintering and heat treatment to re-prepare blanks has developed rapidly as a new green technology, as described in invention patents 201610455267.9 and 201910862247.7. However, the waste magnets not only have a high oxygen content, but also suffer from severe rare earth loss after crushing and powdering again, resulting in a serious reduction in the magnetic properties of the secondary prepared magnets. Therefore, in the preparation process of recycled magnets, a certain amount of rare earth-rich alloy is usually added to supplement the rare earth content and improve the magnetic properties of the recycled magnets, such as adding alloys or single substances of Ce, La, Pr, and Nd as described in invention patents 202310288509.X and 202311435476.3, and adding nano TbH3 particles and Nd-Fe-B magnetic powder with high remanence as described in invention patent 202011324051.1. Although the above method can effectively utilize sintered Nd-Fe-B magnet waste, it still requires additional rare earth content or the addition of high-performance sintered Nd-Fe-B magnetic powder. The prepared recycled magnets not only have low magnetic properties, but also have limited effect on reducing production costs.
[0005] Recently, in the invention patent 202010157867.3, a dual-main-phase alloy process was used to prepare cost-effective rare earth permanent magnet materials. The first main phase is sintered Nd-Fe-B magnet recycled material, with an addition amount of 10-70wt.%; the second main phase is a high-abundance rare earth-based permanent magnet phase with a high total rare earth content (33-37wt.%), of which the high-abundance rare earth elements La, Ce, and Y account for 10-80wt.%; in addition, it may also include a third permanent magnet main phase that does not contain high-abundance rare earths, with a total rare earth content (29-33wt.%); then the initially crushed Nd-Fe-B magnet recycled material and the second main phase and the third main phase rapid solidification flakes are mixed in proportion for hydrogen crushing and air flow grinding to prepare regenerated sintered magnets. This invention patent takes sintered Nd-Fe-B magnet recycled material as the main body, and uses the second main phase and the third main phase to provide the grain boundary phase. However, when the Ce content in the high-abundance rare earth-based second main phase with a high total rare earth content is high, a large amount of CeFe2 grain boundary phase will be generated. When the CeFe2 phase is used as the grain boundary phase in the recycled magnet, it is harmful to the magnetic properties, especially causing a serious reduction in coercivity. In general, in order to obtain higher magnetic properties (as stated in the claims: remanence: 12-14 kG, coercivity 11.9-17 kOe, magnetic energy product: 36-48 MGOe) by using this method to prepare recycled sintered magnets, it is still necessary to use a large amount of non-high-abundance rare earth elements other than La, Ce, and Y, which is not conducive to the balanced utilization of rare earth resources and the further reduction of production costs.
[0006] In summary, on the one hand, in order to reduce the backlog of Ce elements, promote the balanced utilization of rare earth resources, and give full play to its advantages as a high-abundance rare earth resource, on the other hand, in order to make high-value use of sintered Nd-Fe-B magnet waste, there is an urgent need for a new method to use high-abundance rare earth Ce and sintered Nd-Fe-B magnet waste to prepare sintered magnets with high Ce content and maintain high coercive force, so as to achieve the replacement of medium and low-grade magnets. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a high Ce content sintered magnet and a preparation method thereof, by adding sintered Nd-Fe-B magnet waste containing heavy rare earth Dy and Tb and having a coercive force greater than 20kOe to a Ce-rich main phase alloy, and using the sintered Nd-Fe-B magnet waste to provide a high magnetocrystalline anisotropy field (H A ) main phase grains; further control the particle size and sintering process of Ce-rich main phase alloy powder and sintered Nd-Fe-B magnet waste powder, and combine the in-situ diffusion technology to construct a high H A shell layer, thereby realizing the preparation of high Ce content sintered magnets with better magnetic properties using sintered Nd-Fe-B magnet waste.
[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0009] A high Ce content sintered magnet, the high Ce content sintered magnet is composed of a main alloy A and an auxiliary alloy B in a mass ratio of 9-6:1-4, and the sum of the mass ratios of the main alloy A and the auxiliary alloy B is 10;
[0010] The main alloy A is a Ce-rich main phase, and the chemical formula is [Re a Ce 1-a ] x Fe 100-x-y-z M y B z , wherein the Ce content is greater than 22.0wt.%, Re is one or more of Pr and Nd, M is one or more of Nb, Ti, V, Zr, Co, Mn, Ni, Ga, Al, Au, and Cu, and a, x, y, and z satisfy the following relationship: 0.1≤a≤0.3, 32≤x≤34, 0.5≤y≤3, 0.8≤z≤1.0; the auxiliary alloy B is sintered Nd-Fe-B magnet waste, and the sintered Nd-Fe-B magnet waste contains rare earths Dy and Tb and has a coercive force greater than 20kOe.
[0011] The method for preparing a sintered magnet with a high Ce content comprises the following steps:
[0012] (1) According to the chemical formula of the main alloy A, various metal components and other components are selected and placed in a crucible. After the materials are baked under vacuum, argon gas is filled in for melting, and then the materials are poured onto a rotating water-cooled copper roller to prepare a quick-setting sheet;
[0013] (2) subjecting the quick-setting flakes obtained in step (1) to hydrogen crushing treatment to obtain hydrogen crushing coarse powder A after dehydrogenation, and then adding a lubricant and an antioxidant to mix evenly to obtain a mixed coarse powder for later use;
[0014] (3) The mixed coarse powder in the above step (2) is subjected to air flow grinding to obtain fine powder A with an average particle size of 2.5 to 4.0 μm for later use;
[0015] (4) removing the surface coating and impurities from the sintered Nd-Fe-B magnet waste containing heavy rare earths Dy and Tb and having a coercive force greater than 20 kOe, and then crushing it with a jaw crusher, followed by hydrogen crushing, and obtaining hydrogen crushed coarse powder B after dehydrogenation;
[0016] (5) The hydrogen-crushed coarse powder B obtained in step (4) is subjected to a first airflow milling to obtain a preliminary fine powder with an average particle size of 3.5-5.0 μm, and then a lubricant and an antioxidant are added and mixed to obtain a mixed preliminary fine powder;
[0017] (6) subjecting the mixed preliminary fine powder to a second jet milling to obtain fine powder B with an average particle size of 1.0-2.5 μm;
[0018] (7) The fine powder A and the fine powder B are mixed to obtain a mixed fine powder C, and a lubricant and an antioxidant are added to mix evenly, and oriented and formed in a magnetic field with a magnetic field strength of 1.5-2.5T under the protection of an inert gas, and then vacuum packaged and cold isostatically pressed to obtain a green body for use;
[0019] (8) placing the green body into a vacuum sintering furnace for sintering-diffusion coordinated treatment, i.e., firstly keeping the temperature at 960-1000° C. for 5-8 h, then cooling the temperature to 800-900° C. for 2-6 h, and finally cooling the green body to room temperature with argon gas to obtain a multi-phase magnet for standby use;
[0020] (9) The multi-phase magnet is placed in a vacuum sintering furnace for two-stage heat treatment, wherein the first stage heat treatment temperature is 680-780°C for 2-4 hours, and the second stage heat treatment temperature is 390-490°C for 3-6 hours.
[0021] Preferably, in step (1), the rotation speed of the water-cooled copper roller is 1-3 m / s, and the thickness of the quick-setting sheet is 150-350 μm.
[0022] Preferably, in step (2), the amount of lubricant added is 0.05%-0.8% of the total mass of the hydrogen-crushed coarse powder A, and the amount of antioxidant added is 0.05%-1.0% of the total mass of the hydrogen-crushed coarse powder A.
[0023] Preferably, in step (5), the amount of lubricant added is 0.05%-0.8% of the total mass of the preliminary fine powder, and the amount of antioxidant added is 0.05%-1.0% of the total mass of the preliminary fine powder.
[0024] Preferably, in step (7), the amount of lubricant added is 0.05%-0.8% of the total mass of the mixed fine powder C, and the amount of antioxidant added is 0.05%-1.0% of the total mass of the mixed fine powder C.
[0025] The present invention provides a sintered magnet with high Ce content and a preparation method thereof, which has the following advantages compared with the prior art:
[0026] (1) The present invention uses high-abundance rare earth element Ce and sintered Nd-Fe-B magnet waste to prepare sintered magnets with high Ce content, which not only promotes the balanced utilization of rare earth resources, but also solves the problem of recycling sintered Nd-Fe-B magnet waste, which is of great significance in terms of economic efficiency and sustainable development;
[0027] (2) The present invention provides a high H magnet by using a dual-phase alloy process and utilizing sintered Nd-Fe-B magnet waste containing heavy rare earths Dy and Tb and having a coercivity greater than 20 kOe. A The 2:14:1 phase grains are prepared by designing the particle sizes of the two main phase alloy powders so that the main phase grains with smaller particle sizes and rich in heavy rare earths Dy and Tb are evenly dispersed around the Ce-rich main phase grains. During the long-term sintering-diffusion heat treatment, the two main phase grains undergo solid-solid diffusion, forming a Dy and Tb-rich shell layer on the surface of the Ce-rich main phase grains while maintaining a small grain size, thereby significantly improving the coercivity of the multi-main phase Ce-based magnet;
[0028] (3) The high Ce content sintered magnet prepared by the present invention has magnetic properties between those of sintered Nd-Fe-B magnets and permanent ferrites, and has a lower production cost than sintered Nd-Fe-B magnets, thus giving full play to the advantages of high-abundance rare earth resources. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The following lubricants are Nd-Fe-B special lubricant 6# produced by Tianjin Yuesheng New Materials Research Institute;
[0031] The antioxidant is Nd-Fe-B special antioxidant 5# produced by Tianjin Yuesheng New Materials Research Institute.
[0032] Embodiment 1:
[0033] The sintered Nd-Fe-B magnet waste containing heavy rare earths Dy and Tb and having a coercivity greater than 20kOe is used to prepare high Ce content multi-phase magnets:
[0034] According to the nominal composition of the main alloy A (Ce 0.8 Nd 0.2 ) 33.0 Fe bal Al 0.8 Cu 0.5 Co1Ga 0.35 Zr 0.2 B 0.95(wt.%), using a copper roller speed of 1.3 m / s, a quick-setting sheet with a thickness of about 220 μm was prepared. Then the quick-setting sheet was hydrogen-crushed, and after dehydrogenation, a coarsely crushed magnetic powder was obtained, and then 0.06% of a lubricant and 0.08% of an antioxidant were added to the mixture, and the mixture was fully mixed and then jet milled under an inert gas atmosphere to obtain an average particle size of X 50 The jet milled powder A is 3.5 μm.
[0035] Sintered Nd-Fe-B magnet waste of N45UH grade was selected as auxiliary alloy B. The total amount of rare earth detected by ICP was 30.8wt.%, including 1.2wt.% Tb and 2.0wt.% Dy. The surface coating and impurities of the magnet waste were removed in an acidic solution, and then the magnet waste was coarsely crushed by a jaw crusher. Then, the coarsely crushed powder was subjected to hydrogen crushing treatment. After dehydrogenation, the hydrogen-crushed coarse powder was obtained. Then, the hydrogen-crushed coarse powder was subjected to the first air flow milling to obtain an average particle size of X 50 The powder was 4.3 μm in size, and then 0.08% of lubricant and 0.10% of antioxidant were added and mixed thoroughly. Then the powder was subjected to a second air flow milling process to obtain an average particle size of X 50 The fine powder B is 1.8 μm.
[0036] In a glove box, the jet milled powders of components A and B were mixed in a mass ratio of 7.5:2.5, and then 0.10% of lubricant and 0.14% of antioxidant were added and mixed uniformly to obtain jet milled powder C with a Ce content of 19.8wt.%. Under an inert gas protective atmosphere, the jet milled powder C was oriented and formed in a magnetic field with a magnetic field strength of 2.0T to obtain a compact. The compact was vacuum packaged and cold isostatically pressed and then placed in a vacuum sintering furnace for sintering-diffusion process coordinated treatment, first at 980℃ for 6 hours, then lowered to 880℃ for 4 hours and then cooled to room temperature with argon gas; then two-step heat treatment was performed at low temperature, first at 740℃ for 3 hours and then cooled to room temperature with argon gas, then at 400℃ for 4 hours and then cooled to room temperature with argon gas, to obtain a multi-phase magnet C, which was placed in a BH tester to test the magnetic properties, and the results are as follows:
[0037] Magnet C: B r =11.07kG, H cj =10.53kOe, (BH) max =29.43MGOe, H k / H cj =96.9%.
[0038] Embodiment 2:
[0039] The sintered Nd-Fe-B magnet waste containing heavy rare earths Dy and Tb and having a coercivity greater than 20kOe is used to prepare high Ce content multi-phase magnets:
[0040] According to the nominal composition of the main alloy A1 (Ce 0.7 Nd 0.3 ) 33.0 Fe bal Al 0.8 Cu 0.5 Co1Ga 0.35 Zr 0.2 B 0.95 (wt.%), using a copper roller speed of 1.3 m / s, a quick-setting sheet with a thickness of about 220 μm was prepared. Then the quick-setting sheet was hydrogen-crushed, and after dehydrogenation, a coarsely crushed magnetic powder was obtained, and then 0.06% of a lubricant and 0.08% of an antioxidant were added to the mixture, and the mixture was fully mixed and then jet milled under an inert gas atmosphere to obtain an average particle size of X 50 The jet milled powder A1 is 3.5 μm.
[0041] Sintered Nd-Fe-B magnet waste of N45UH grade was selected as auxiliary alloy B. The total amount of rare earth detected by ICP was 30.8wt.%, including 1.2wt.% Tb and 2.0wt.% Dy. The surface coating and impurities of the magnet waste were removed in an acidic solution, and then the magnet waste was coarsely crushed by a jaw crusher. Then the coarsely crushed powder was subjected to hydrogen crushing treatment. After dehydrogenation, the hydrogen-crushed coarse powder was obtained. Then, the hydrogen-crushed coarse powder was subjected to the first air flow milling to obtain an average particle size of X 50 The powder was 4.3 μm in size, and then 0.08% of lubricant and 0.10% of antioxidant were added and mixed thoroughly. Then the powder was subjected to a second air flow milling process to obtain an average particle size of X 50 The fine powder B is 1.8 μm.
[0042] In a glove box, the jet-milled powders of components A1 and B were mixed in a mass ratio of 7.0:3.0, and then 0.10% of a lubricant and 0.14% of an antioxidant were added thereto and mixed evenly to obtain jet-milled powder C1 with a Ce content of 16.17 wt.%.
[0043] Under an inert gas protective atmosphere, the jet milled powder C1 was oriented and formed in a magnetic field with a magnetic field strength of 2.0T to obtain a green compact. The green compact was vacuum packaged and cold isostatically pressed, and then placed in a vacuum sintering furnace for sintering-diffusion process coordinated treatment. It was first kept at 980°C for 6 hours, then lowered to 880°C for 4 hours, and then cooled to room temperature with argon gas; then a two-step heat treatment was performed at low temperature, first at 740°C for 3 hours, then cooled to room temperature with argon gas, and then at 400°C for 4 hours, then cooled to room temperature with argon gas, to obtain a multi-phase magnet C1, which was placed in a BH tester to test the magnetic properties. The results are as follows:
[0044] Magnet C1: B r =11.35kG, H cj =12.48kOe, (BH) max =31.08MGOe, H k / H cj =96.7%.
[0045] Embodiment 3:
[0046] The sintered Nd-Fe-B magnet waste containing heavy rare earths Dy and Tb and having a coercivity greater than 20kOe is used to prepare high Ce content multi-phase magnets:
[0047] According to the nominal composition of the main alloy A1 (Ce 0.7 Nd 0.3 ) 33.0 Fe bal Al 0.8 Cu 0.5 Co1Ga 0.35 Zr 0.2 B 0.95 (wt.%), using a copper roller speed of 1.3 m / s, a quick-setting sheet with a thickness of about 220 μm was prepared. Then the quick-setting sheet was hydrogen-crushed, and after dehydrogenation, a coarsely crushed magnetic powder was obtained, and then 0.06% of a lubricant and 0.08% of an antioxidant were added to the mixture, and the mixture was fully mixed and then jet milled under an inert gas atmosphere to obtain an average particle size of X 50 The jet milled powder A1 is 3.5 μm.
[0048] Sintered Nd-Fe-B magnet waste of N40EH grade was selected as auxiliary alloy B1. The total amount of rare earth detected by ICP was 31.5wt.%, including 3.5wt.% Dy and 1.5wt.% Tb. The surface coating and impurities of the magnet waste were removed in an acidic solution, and then the magnet waste was coarsely crushed by a jaw crusher. Then, the coarsely crushed powder was subjected to hydrogen crushing treatment. After dehydrogenation, the hydrogen-crushed coarse powder was obtained. Then, the hydrogen-crushed coarse powder was subjected to the first air flow milling to obtain an average particle size of X 50The powder was 4.3 μm in size, and then 0.08% of lubricant and 0.10% of antioxidant were added and mixed thoroughly. Then the powder was subjected to a second air flow milling process to obtain an average particle size of X 50 The fine powder B1 is 1.8 μm.
[0049] In a glove box, the airflow-milled powders of components A1 and B1 were mixed in a mass ratio of 7.0:3.0, and then 0.10% of a lubricant and 0.14% of an antioxidant were added thereto and mixed evenly to obtain airflow-milled powder C2 with a Ce content of 16.17 wt.%.
[0050] Under an inert gas protective atmosphere, the air flow milled powder C2 is oriented and formed in a magnetic field with a magnetic field strength of 2.0T to obtain a green compact. The green compact is vacuum packaged and cold isostatically pressed, and then placed in a vacuum sintering furnace for sintering-diffusion process coordinated treatment. First, it is kept at 980℃ for 6 hours, then the temperature is reduced to 880℃ and kept for 4 hours, and then cooled to room temperature with argon gas; then a two-step heat treatment is performed at low temperature, first at 740℃ for 3 hours, then cooled to room temperature with argon gas, and then at 400℃ for 4 hours, then cooled to room temperature with argon gas, to obtain a multi-phase magnet C2, which is placed in a BH tester to test the magnetic properties. The results are as follows:
[0051] Magnet C2: B r =11.22kG, H cj =14.07kOe, (BH) max =30.24MGOe, H k / H cj =96.3%.
[0052] Comparative Example 1:
[0053] The traditional dual alloy process is used to prepare high Ce content multi-phase magnets:
[0054] According to the nominal composition of the main alloy A (Ce 0.8 Nd 0.2 ) 33.0 Fe bal Al 0.8 Cu 0.5 Co1Ga 0.35 Zr 0.2 B 0.95 (wt.%), based on the nominal composition Nd of auxiliary alloy B2 31 Fe bal Al 0.1 Cu 0.5 Co 0.8 Ga 0.35 Zr 0.2 B 0.95(wt.%), and a copper roller speed of 1.3 m / s was used to prepare quick-setting sheets of components A and B2 with a thickness of about 220 μm.
[0055] The quick-setting flakes of components A and B2 were hydrogen-crushed to obtain coarsely crushed magnetic powder after dehydrogenation. Then, 0.06% lubricant and 0.08% antioxidant were added to the mixture in a mass ratio and then jet milled under an inert gas atmosphere to obtain jet milled fine powders of components A and B2. The average particle size of the jet milled powder of component A was X 50 The average particle size of the jet milled powder of component B2 is 3.5 μm. 50 It is 2.6μm.
[0056] In the glove box, 0.12% of lubricant and 0.16% of antioxidant were added to the airflow milled powders of components A and B2 respectively and mixed evenly. Then, the airflow milled powders of components A and B2 were mixed in a mass ratio of 7.5:2.5 to obtain airflow milled powder C3 with a Ce content of 19.8wt.%.
[0057] Under an inert gas protective atmosphere, the jet milled powder C3 was oriented and formed in a magnetic field with a magnetic field strength of 2.0T to obtain a green compact. The green compact was vacuum packaged and cold isostatically pressed, and then placed in a vacuum sintering furnace for conventional sintering process. After the sintering temperature was kept at 1010℃ for 5 hours, it was cooled to room temperature with argon gas. Then, two steps of conventional heat treatment were carried out, firstly, it was kept at 820℃ for 3 hours, then cooled to room temperature with argon gas, and then it was kept at 400℃ for 4 hours, then cooled to room temperature with argon gas. The multi-phase magnet C3 was obtained, and the magnetic properties were tested in a BH tester. The results are as follows:
[0058] Magnet C3: B r =11.17 kG, H cj =6.54kOe, (BH) max =28.76MGOe, H k / H cj =96.2%.
[0059] Comparative Example 2:
[0060] The traditional dual alloy process combined with sintering-in-situ diffusion heat treatment is used to prepare high Ce content multi-phase magnets:
[0061] According to the nominal composition of the main alloy A (Ce 0.8 Nd 0.2 ) 33.0 Fe bal Al 0.8 Cu 0.5 Co1Ga 0.35 Zr 0.2 B 0.95(wt.%), based on the nominal composition Nd of auxiliary alloy B2 31 Fe bal Al 0.1 Cu 0.5 Co 0.8 Ga 0.35 Zr 0.2 B 0.95 (wt.%), and a copper roller speed of 1.3 m / s was used to prepare quick-setting sheets of components A and B2 with a thickness of about 220 μm.
[0062] The quick-setting flakes of components A and B2 were hydrogen-crushed to obtain coarsely crushed magnetic powder after dehydrogenation. Then, 0.06% lubricant and 0.08% antioxidant were added to the mixture in a mass ratio and then jet milled under an inert gas atmosphere to obtain jet milled fine powders of components A and B2. The average particle size of the jet milled powder of component A was X 50 The average particle size of the jet milled powder of component B2 is 3.5 μm. 50 It is 2.6μm.
[0063] In the glove box, 0.12% of lubricant and 0.16% of antioxidant were added to the airflow milled powders of components A and B2 respectively and mixed evenly. Then, the airflow milled powders of components A and B2 were mixed in a mass ratio of 7.5:2.5 to obtain airflow milled powder C3 with a Ce content of 19.8wt.%.
[0064] Under an inert gas protective atmosphere, the air flow milled powder C3 is oriented and formed in a magnetic field with a magnetic field strength of 2.0T to obtain a green compact. The green compact is vacuum packaged and cold isostatically pressed, and then placed in a vacuum sintering furnace for sintering-diffusion process coordinated treatment. First, it is kept at 980℃ for 6 hours, then the temperature is reduced to 880℃ and kept for 4 hours, and then cooled to room temperature with argon gas; then a two-step heat treatment is performed at low temperature, first at 740℃ for 3 hours, then cooled to room temperature with argon gas, and then at 400℃ for 4 hours, then cooled to room temperature with argon gas, to obtain a multi-phase magnet C4, which is placed in a BH tester to test the magnetic properties. The results are as follows:
[0065] Magnet C4: B r =11.13kG, H cj =7.26kOe, (BH) max =29.23MGOe, H k / H cj =97.3%.
[0066] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high Ce content sintered magnet, characterized in that: The high Ce content sintered magnet is composed of a main alloy A and an auxiliary alloy B in a mass ratio of 9-6:1-4, and the sum of the mass ratios of the main alloy A and the auxiliary alloy B is 10; The main alloy A is a Ce-rich main phase, and the chemical formula is [Re a Ce 1-a ] x Fe 100-x-y-z M y B z , wherein the Ce content is greater than 22.0wt.%, Re is one or more of Pr and Nd, M is one or more of Nb, Ti, V, Zr, Co, Mn, Ni, Ga, Al, Au, and Cu, and a, x, y, and z satisfy the following relationship: 0.1≤a≤0.3, 32≤x≤34, 0.5≤y≤3, 0.8≤z≤1.0; the auxiliary alloy B is sintered Nd-Fe-B magnet waste, and the sintered Nd-Fe-B magnet waste contains rare earths Dy and Tb and has a coercive force greater than 20kOe.
2. A method for preparing a sintered magnet with a high Ce content as claimed in claim 1, characterized in that: The preparation method comprises the following steps: (1) According to the chemical formula of the main alloy A, various metal components and other components are selected and placed in a crucible. After the materials are baked under vacuum, argon gas is filled in for melting, and then the materials are poured onto a rotating water-cooled copper roller to prepare a quick-setting sheet; (2) subjecting the quick-setting flakes obtained in step (1) to hydrogen crushing treatment to obtain hydrogen crushing coarse powder A after dehydrogenation, and then adding a lubricant and an antioxidant to mix evenly to obtain a mixed coarse powder for later use; (3) The mixed coarse powder in the above step (2) is subjected to air flow grinding to obtain fine powder A with an average particle size of 2.5 to 4.0 μm for later use; (4) removing the surface coating and impurities from the sintered Nd-Fe-B magnet waste containing heavy rare earths Dy and Tb and having a coercive force greater than 20 kOe, and then crushing it with a jaw crusher, followed by hydrogen crushing, and obtaining hydrogen crushed coarse powder B after dehydrogenation; (5) The hydrogen-crushed coarse powder B obtained in step (4) is subjected to a first airflow milling to obtain a preliminary fine powder with an average particle size of 3.5-5.0 μm, and then a lubricant and an antioxidant are added and mixed to obtain a mixed preliminary fine powder; (6) subjecting the mixed preliminary fine powder to a second jet milling to obtain fine powder B with an average particle size of 1.0-2.5 μm; (7) The fine powder A and the fine powder B are mixed to obtain a mixed fine powder C, and a lubricant and an antioxidant are added to mix evenly, and oriented and formed in a magnetic field with a magnetic field strength of 1.5-2.5T under the protection of an inert gas, and then vacuum packaged and cold isostatically pressed to obtain a green body for use; (8) placing the green body into a vacuum sintering furnace for sintering-diffusion coordinated treatment, i.e., firstly keeping the temperature at 960-1000° C. for 5-8 h, then cooling the temperature to 800-900° C. for 2-6 h, and finally cooling the green body to room temperature with argon gas to obtain a multi-phase magnet for standby use; (9) The multi-phase magnet is placed in a vacuum sintering furnace for two-stage heat treatment, wherein the first stage heat treatment temperature is 680-780°C for 2-4 hours, and the second stage heat treatment temperature is 390-490°C for 3-6 hours.
3. The preparation method according to claim 2, characterized in that: In the step (1), the rotation speed of the water-cooled copper roller is 1-3 m / s, and the thickness of the quick-setting sheet is 150-350 μm.
4. The preparation method according to claim 2, characterized in that: In the step (2), the amount of lubricant added is 0.05%-0.8% of the total mass of the hydrogen-crushed coarse powder A, and the amount of antioxidant added is 0.05%-1.0% of the total mass of the hydrogen-crushed coarse powder A.
5. The preparation method according to claim 2, characterized in that: In the step (5), the amount of lubricant added is 0.05%-0.8% of the total mass of the preliminary fine powder, and the amount of antioxidant added is 0.05%-1.0% of the total mass of the preliminary fine powder.
6. The preparation method according to claim 2, characterized in that: In the step (7), the amount of lubricant added is 0.05%-0.8% of the total mass of the mixed fine powder C, and the amount of antioxidant added is 0.05%-1.0% of the total mass of the mixed fine powder C.
Citation Information
Patent Citations
Low-cost dual-phase Ce permanent magnet alloy and its preparation method
CN102800454B
A kind of rare earth permanent magnet alloy and its magnetic phase compound preparation method
CN103187133B
Recycling method for recycled waste material of sintered neodymium iron boron
CN105931781A
A method for recycling sintered NdFeB waste
CN110480020B
A high-performance rare earth permanent magnet and its preparation method
CN111341512B